2 Rois 14:27 et l'influence des livres proph tiques sur la r daction du deuxi me livre des Rois - Gosse, Bernard 1949- (1994)
It is argued that the redactors of 2 Kings were influenced by the prophetic books of Amos and Isaiah to portray the history of the kingdom of Judah and its destruction as a parallel to that of Israel and as the fulfilment of the prophecies of God's servants the prophets.
Keywords: 2 Kings; Amos; Fulfilment of the prophecies; Isaiah; Prophetic Books; kingdom of Judah